2015
DOI: 10.4062/biomolther.2015.024
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative Effect of Naringenin through p38-Dependent Downregulation of Cyclin D1 in Human Colorectal Cancer Cells

Abstract: Naringenin (NAR) as one of the flavonoids observed in grapefruit has been reported to exhibit an anti-cancer activity. However, more detailed mechanism by which NAR exerts anti-cancer properties still remains unanswered. Thus, in this study, we have shown that NAR down-regulates the level of cyclin D1 in human colorectal cancer cell lines, HCT116 and SW480. NAR inhibited the cell proliferation in HCT116 and SW480 cells and decreased the level of cyclin D1 protein. Inhibition of proteasomal degradation by MG132… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The synthesis of AgNPs was carried out using a pure aqueous solution of NAR (50 µM) mixed with 2 mM silver nitrate at 37 °C for 1 h. NAR is a flavonoid with significant antibiotic, anti-cancerous, and anti-inflammatory properties against various types of cancer cells [26,27,28]. Color formation rapidly occurred in this mixture, possibly because of the reaction between Ag ions and NAR [12,28].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of AgNPs was carried out using a pure aqueous solution of NAR (50 µM) mixed with 2 mM silver nitrate at 37 °C for 1 h. NAR is a flavonoid with significant antibiotic, anti-cancerous, and anti-inflammatory properties against various types of cancer cells [26,27,28]. Color formation rapidly occurred in this mixture, possibly because of the reaction between Ag ions and NAR [12,28].…”
Section: Resultsmentioning
confidence: 99%
“…There are observations indicating that ATF3 inhibits cancer cell proliferation through activating p53 ( Yan et al ., 2005 ; Wang et al ., 2010 ) and downregulating cyclin D1 by transcriptional suppression ( Lu et al ., 2006b ). We have reported that NAR downregulates cyclin D1 protein level but not mRNA level resulting in the growth arrest of human colon cancer cells ( Song et al ., 2015 ), which indicates that NAR-mediated downregulation of cyclin D1 may be independent on ATF3 activation. Although ATF3 has been regarded as a common molecular target for the proapoptotic effect, specific mechanisms for the apoptotic effect of ATF3 remain nuclear.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenantibody complexes were detected using ECL reagents with an ImageQuant LAS-4000 mini (GE Healthcare Life Sciences, Piscataway, NJ, USA). GAPDH or β-actin was used as the loading control (12).…”
Section: Methodsmentioning
confidence: 99%